Telenursing Applications in Treatment Compliance among Patients with Mental Disorders - Noorwahyu Trihidayat; Mamnuah Mamnuah; Yuli Isnaeni (Universitas Aisyiyah Yogyakarta, 2023)
Background: Treatment adherence is one of the problems in the treatment of patients with mental disorders. Telenursing is a part of telemedicine that plays an important role in providing modern nursing care, improving the quality of care, and accessing services quickly. Purpose: To describe the use of telenursing in medication adherence in patients with mental disorders. Methods: Literature review searches were conducted on PubMed, Wiley, and Google scholar. The search strategy used the keywords